1978
DOI: 10.1037/0021-9010.63.5.596
|View full text |Cite
|
Sign up to set email alerts
|

An eight-year follow-up of a management assessment center.

Abstract: Forty-seven individuals evaluated in a management assessment center in 1967 in the marketing organization of a large manufacturing company were followed up 8 years later. Both the overall assessment center rating and a general management evaluation of potential derived from personnel files were significantly related to position level attained after 8 years for 30 individuals still with the company. The shrunken multiple correlation of these two predictors with level attained was .58. Characteristics of aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 4 publications
1
49
1
3
Order By: Relevance
“…Positive career impact was also a strong theme, building upon existing quantitative-empirical studies with similar findings (Hinrichs, 1978;Ritchie, 1994). Many participants gained new roles and the remainder were able to demonstrate increased responsibilities, including those who failed the Centre.…”
Section: Enabling Changing and Taking Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive career impact was also a strong theme, building upon existing quantitative-empirical studies with similar findings (Hinrichs, 1978;Ritchie, 1994). Many participants gained new roles and the remainder were able to demonstrate increased responsibilities, including those who failed the Centre.…”
Section: Enabling Changing and Taking Actionmentioning
confidence: 99%
“…In recent years, Development Centres have become more commonplace in personal and career development (Goodge, 1994;Hart, 1979;Hinrichs, 1978;Thornton and Krause, 2009;Tillema, 1998;Vloeberghs and Bergham, 2003;Wilson, 1996).…”
Section: Development and Assessment Centresmentioning
confidence: 99%
“…For noncognitive predictors studied thus far, such as assessment center ratings, criterion-related validities tend to be better in the long run. For example, Hinrichs (1978) found that assessment center ratings predicted organizational level better 8 years postassessment than 1 year postassessment. Similar patterns of results have been reported by Bray and Howard (1983) and more recently by Jansen and Stoop (2001).…”
Section: Research On Longitudinal Changes In Criteriamentioning
confidence: 99%
“…using longitudinal designs. Hinrichs (1978) reported that aggressiveness measured during assessment center exercises predicted organizational level better after 8 years on the job than earlier. Other studies (Dodd et al, 1970;Helmreich et al, 1986;Singh, 1978) all reported higher long-term validities of specific personality scales for job performance.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Past empirical research suggests that management's ratings from the assessment center, along with the management evaluations of promotion potential, are important tools to predict employees' promotion and advancement in the organization (Hinrichs, 1969;1978). Recently, there has been an increasing trend for large corporations to dedicate efforts to the HiPo assessment and development (Church, Rotolo, Ginther, & Levine, 2015).…”
Section: Identification Of Hipo Employees and Challengesmentioning
confidence: 99%